CD109, a master regulator of inflammatory responses - Batal, Adel; Garousi, Setareh; Finnson, Kenneth W.; Philip, Anie (Frontiers in Immunology, 2025)
Inflammation is a complex response to harmful stimuli, crucial for immunity, and linked to chronic diseases and cancer, with TGF-β and NF-κB pathways as key regulators. CD109 is a glycosylphosphatidylinositol (GPI)-anchored protein, that our group has originally identified as a TGF-β co-receptor and inhibitor of TGF-β signaling. CD109 modulates TGF-β and NF-κB pathways, to influence immune responses and inflammation. CD109’s multifaceted role in inflammation spans various tissue types, including the skin, lung, bone and bone-related tissues, and various types of cancers. CD109 exerts its effects by modulating processes such as cytokine secretion, immune cell recruitment, macrophage polarization, T helper cell function and cancer cell phenotype and function. Here, we review CD109’s regulatory functions in inflammatory responses in these various tissues and cell types. Exploration of CD109’s mechanisms of action will enhance our understanding of its contributions to disease pathology and its potential for therapeutic applications.